Implementasi Mata Pelajaran Pendidikan Agama Islam Kelas 1 Dalam Kurikulum Merdeka di SDN Sukamantri 2 - Trisna, Lelih; Gozali, Laili Rizki Nurilahi; Suryadi, Rudi Ahmad (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research is motivated by the change in the 2013 curriculum with the Merdeka curriculum. The purpose of this research is to find out how the implementation of Islamic religious education lessons in the independent curriculum in grade 1 (low grade). This research comes from teachers, principals, and supervisors. The research was conducted using a qualitative method, namely by collecting data from observations, interviews, and documentation. To ensure the validity of the data, several efforts are made as follows: (a) extending the data collection period, (b) make continuous and serious observations, (c) perform triangulation, and (d) involve colleagues to discuss. From this, it turns out that there are still many people who reject this change in curriculum. This curriculum change was considered very sudden. Many students complain due to the large number of presentation assignments at school, the large number of group work assignments outside of class hours, even though learning with this independent curriculum is considered more relaxed, and the material provided is also less. However, in the future students will be faced with other students who study more material such as students in the 2013 curriculum, so students with an independent curriculum will be left behind. The independent curriculum focuses on character development, student competence, and honing children's interests and talents. From this change in the independent curriculum, many students rejected the existence of this curriculum, because this change was considered very sudden.